2017
DOI: 10.1002/ana.24981
|View full text |Cite
|
Sign up to set email alerts
|

Gene therapy decreases seizures in a model of Incontinentia pigmenti

Abstract: The data show that the BBB is a target of antiepileptic treatment and, more specifically, provide evidence for the therapeutic benefit of a brain endothelial-targeted gene therapy in IP. Ann Neurol 2017;82:93-104.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
23
2

Year Published

2017
2017
2025
2025

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 23 publications
(28 citation statements)
references
References 40 publications
(152 reference statements)
3
23
2
Order By: Relevance
“…This dose proved to be efficacious in previous studies. 22,23 For the treatment of neonatal Hexb À/À mice with the vectors, AAV-BR1-CAG-HEXA/B and AAV-BR1-CAG-Ø were injected intravenously into the temporal vein using a stereo microscope. Owing to increased lethality and neurotoxicity of isoflurane, neonatal mice were not anesthetized.…”
Section: Intravenous Injection Of Aav-br1-cag-hexa/b and Aav-br1-cag-mentioning
confidence: 99%
See 1 more Smart Citation
“…This dose proved to be efficacious in previous studies. 22,23 For the treatment of neonatal Hexb À/À mice with the vectors, AAV-BR1-CAG-HEXA/B and AAV-BR1-CAG-Ø were injected intravenously into the temporal vein using a stereo microscope. Owing to increased lethality and neurotoxicity of isoflurane, neonatal mice were not anesthetized.…”
Section: Intravenous Injection Of Aav-br1-cag-hexa/b and Aav-br1-cag-mentioning
confidence: 99%
“…21 We have developed a unique AAV vector (AAV-BR1) which, when systemically administered, is capable of transducing CNS endothelial cells and leading to a sustained gene expression. 22,23 Importantly, AAV-BR1 shows an unprecedented degree of selectivity for the CNS endothelium over other cell types, resulting in a favorable safety profile. 22,23 Here, we show that by intravenously injecting the AAV-BR1 vector for expressing human HEXA and HEXB in CNS endothelial cells of Hexb À/À mice, we were able to increase b-hexosaminidase A activity, decrease lysosomal storage of GM2 and GA2, and prolong survival.…”
Section: Introductionmentioning
confidence: 99%
“…Mice treated with AAV-BR1-Nemo showed less activation of astrocytes. Importantly, the occurrence of focal epileptic seizures was significantly reduced by the gene therapy [ 26 ]. Probably due to its high brain endothelial selectivity, the vector did not induce hepatocellular carcinoma or other adverse effects that have been observed in rodents during gene therapy with AAV vectors.…”
Section: The Blood–brain Barrier In Gene Therapy: Hurdle or Target?mentioning
confidence: 99%
“…The data obtained may be used for family genetic counseling as well as guiding the treatment approaches and predicting the prognosis. With increasing availability of genetic diagnosis, precision therapy will also be an option of management for neonatal-onset epilepsy 12 . For example, encoding a voltage-gated potassium channel, electro-physiological analysis showed that the majority of KCNQ2 mutations lead to an increase in potassium current, which may be treated by retigabine to reduce the current amplitude or to depolarize shift of the activation curve 13, 14…”
Section: Discussionmentioning
confidence: 99%